Applying Research in Special Library Settings. Issue 4 (18th May 2016) - Murray, Tara E.
ABSTRACT: Special librarians encourage their users to base decisions on vetted research results and quality information, yet when faced with a problem in their own work, they are more likely to turn to their network of colleagues than to published research. While learning from the experience of colleagues is valuable, greater application of research and evidence-based practice in the special library sector could benefit these libraries in making good, strategic decisions. A few studies have examined whether practitioners use library and information science research and what barriers keep them from doing so. Engaging practitioners and scholars in productive collaboration and communication can help practitioners find and apply lessons learned from research in their work and encourage more participation in research by special librarians. In turn, increased diversity in research settings can benefit all libraries as they evolve and learn from each other's experiences.